Human behaviour in household energy use and the implications of energy efficiency delivery: a case of Bauchi, Nigeria - Hussaini, Ibrahim Udale; Abdul Majid, Noor Hanita (Emerald Insight, 2014)
Purpose – Although the term “energy efficiency” is technologically focused, it has a behavioural content due to the associated energy conservation practice involved. The technology aspect applies essentially to the application of new or better technology in order to derive same output or level of service for less input energy, while the conservation aspect is attributed to behaviour. The paper aims to discuss these issues.